Agroforestry in south of Kurdistan : with focus on improving soil organic matter and soil structure - Johansson, Magnus (SLU/Horticulture (until 121231), 2012)
The area in and around Iraq is formerly known as Mesopotamia and is the birthplace of agriculture. The agriculture in south of Kurdistan, northern Iraq, is today being threatened by drought and depletion, and access to knowledge is limited in these regions. How can agriculture develop in the future without making too big impact on the environment? The main question was in what ways is it possible to use multifunctional plant species for increasing soil organic matter and improving soil structure in Kurdistan? Growing trees, shrubs and crops together and sometimes in combination with livestock is called agroforestry. Agroforestry can be divided in several systems where alley cropping was chosen due to its ability to be applied to farms of both small and big size. Trees and shrubs can be used to improve soil structure and increase soil organic matter. By pruning woody plants and add to the soil as litter or mulch it can increase the soil organic matter. Roots contribute with organic matter when penetrating the soil. Trees with a higher production of biomass should be chosen since they give a higher amount of litter that could be added to the soil. One thing that became clear was that no matter what species of trees were used, the soil organic matter increased when mulching. The outcome of these investigations showed that some of the keys to long-time fertility were to carefully select what species is the most suitable for the goal at the chosen site. In this case I found that Punica granatum and Carissa edulis was the best choice of lignified species at my site. These species were chosen mostly because of the adaption to the arid climate but also due to the difficulty to find other multifunctional species. Evergreen trees in arid areas use a lot of water, why species like Eucalyptus should be avoided in agroforestry systems. Hopefully this written thesis will be an inspiration for farmers that wish to sustain their soil fertility and increase biodiversity, and to do so in line with nature instead of depleting the soil. I wish my thesis will gain and inspirit the Kurdish people whom I have gotten so much inspiration and love from in return.